2010
DOI: 10.4049/jimmunol.1000532
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 and Rig-Like Receptor on Myeloid Dendritic Cells and Rig-Like Receptor on Human NK Cells Are Both Mandatory for Production of IFN-γ in Response to Double-Stranded RNA

Abstract: Cross-talk between NK cells and dendritic cells (DCs) is critical for the potent therapeutic response to dsRNA, but the receptors involved remained controversial. We show in this paper that two dsRNAs, polyadenylic-polyuridylic acid and polyinosinic-polycytidylic acid [poly(I:C)], similarly engaged human TLR3, whereas only poly(I:C) triggered human RIG-I and MDA5. Both dsRNA enhanced NK cell activation within PBMCs but only poly(I:C) induced IFN-γ. Although myeloid DCs (mDCs) were required for NK cell activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 45 publications
5
90
0
Order By: Relevance
“…Not only an increased cellularity of dLNs but also an enhanced activation of various cell types including B cells, T cells, migratory DCs, NK cells and NKT cells following the adjuvant injection was observed. Similar phenomenon was observed after the use of a TLR agonist such as R848 43 suggesting that RNAdjuvant 44,45 Using a murine model of HPV-16-induced cervical cancer we demonstrated that vaccination with low doses of the previously described HPV-E7-derived peptide containing both, a CTL epitope (E7 [49][50][51][52][53][54][55][56][57] ) and a Th epitope, 24 led to a complete eradication of established tumors in combination with RNAdjuvant V R . Similar results were obtained by Zwaveling and colleagues using E7 peptide combined with CpG.…”
Section: Rnadjuvantmentioning
confidence: 67%
See 2 more Smart Citations
“…Not only an increased cellularity of dLNs but also an enhanced activation of various cell types including B cells, T cells, migratory DCs, NK cells and NKT cells following the adjuvant injection was observed. Similar phenomenon was observed after the use of a TLR agonist such as R848 43 suggesting that RNAdjuvant 44,45 Using a murine model of HPV-16-induced cervical cancer we demonstrated that vaccination with low doses of the previously described HPV-E7-derived peptide containing both, a CTL epitope (E7 [49][50][51][52][53][54][55][56][57] ) and a Th epitope, 24 led to a complete eradication of established tumors in combination with RNAdjuvant V R . Similar results were obtained by Zwaveling and colleagues using E7 peptide combined with CpG.…”
Section: Rnadjuvantmentioning
confidence: 67%
“…Indeed, E7 [49][50][51][52][53][54][55][56][57] peptide-specific CD8 1 T-cell responses induced by E7 peptide/RNAdjuvant V R vaccination were significantly higher than those triggered by E7 peptide/Poly(I:C) as determined by ICS and HPV-16-E7 pentamer staining (Figs. 3e and 3f, respectively).…”
Section: Having Demonstrated That Rnadjuvantmentioning
confidence: 99%
See 1 more Smart Citation
“…However, monophosphoryl lipid A still retains the TLR4-mediated MyD88 activation, which conceptually different from sODN-dsRNA that activates a single cascade of PRR. Although poly(A:U) mildly activates the TLR3 pathway and induces type I IFN in humans 47 , it has far less adjuvancy than poly(I:C) 6,28,48 . In a short-term clinical trial, poly(I:C 12 U), also known as ampligen, has been shown to be less toxic than other immunotherapies 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several adjuvants that are able to interact with more than one PRR. For example, poly(I:C), a synthetic analogue of double-stranded RNA, binds TLR3, MDA5 and RIG-I [78]. In addition, it has been shown that for an efficient immune activation, interaction with both TLR3 ad RLRs is necessary [79].…”
Section: In Vivo Targeting Of Antigens and Adjuvant-activation Of Denmentioning
confidence: 99%